Decision making profile : a study of six secondary school head teachers in Sarawak - Siti Mariam, Abdullah (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Decision making is an essential tactical skill for effective leaders in all organisations. In today's environment, there are many demands and high expectations of schools from the stakeholders in national education; external and internal. In their midst, head teachers who are subjected to such demands as well as constraints, have to make judgements and choices leading to a variety of decisions made. It is within these decision making processes that opportunities are created for head teachers to display excellence in managing their schools and distinguish between exemplary and mediocre school leaders.